Acute upper gastrointestinal bleeding in patients with AIDS: a relatively uncommon condition associated with reduced survival. Issue 9 (September 1991) - Parente, F; Cernuschi, M; Valsecchi, L; Rizzardini, G; Musicco, M; Lazzarin, A; Bianchi Porro, G
Abstract : To determine the cumulative incidence of acute upper gastrointestinal bleeding and its effect upon survival in patients with AIDS, 453 consecutive AIDS patients diagnosed in our hospital between June 1985 and March 1989 were followed for a median period of six months (maximum 42 months). The cumulative probability of acute gastrointestinal bleeding was 3% at six months and 6% at 14 months. This event was associated with significantly reduced survival. Independent risk factors for bleeding were: severe thrombocytopenia at the time of diagnosis and non-Hodgkin's lymphoma as the first clinical manifestation of AIDS. The potential causes of bleeding were investigated in all cases by emergency endoscopy or by necropsy examination in those patients whose clinical condition precluded the procedure. In nine of 15 patients, bleeding was due to lesions specifically associated with AIDS, but in the remainder the source of bleeding was not a direct consequence of HIV infection. We conclude that acute upper gastrointestinal bleeding rarely complicates the course of AIDS, but its occurrence is associated with decreased survival. As many of the causes are potentially treatable, a complete diagnostic approach is indicated in these patients, except those who are terminally ill.